1998
DOI: 10.1046/j.1365-2133.1998.02410.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of female sex hormones on skin thickness: evaluation using 20 MHz sonography

Abstract: Changes in skin thickness and echodensity during the spontaneous menstrual cycle, in women taking hormonal contraceptives and pregnant women were investigated by high-frequency (20 MHz) ultrasound. Women with a spontaneous ovulatory menstrual cycle (group I), women taking one-phase contraceptives (group II), women taking three-phase contraceptives (group III) and pregnant women (group IV) were measured at the following locations: proximal and distal forearm and lower leg on both sides. The skin was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 21 publications
2
41
2
1
Order By: Relevance
“…The number of cell layers has been reported to increase slightly with age especially in men [39]. The positive influence of estrogens on skin thickness in females has also been shown [40][41][42]. Other factors that influence the corneocyte size, such as UV irradiation [43] and corticosteroid application [44], both lead to a decrease in corneocyte size.…”
Section: Discussionmentioning
confidence: 99%
“…The number of cell layers has been reported to increase slightly with age especially in men [39]. The positive influence of estrogens on skin thickness in females has also been shown [40][41][42]. Other factors that influence the corneocyte size, such as UV irradiation [43] and corticosteroid application [44], both lead to a decrease in corneocyte size.…”
Section: Discussionmentioning
confidence: 99%
“…formation of a greater true contact area) upon the iterative soaking procedure. Greater epidermal and dermal thickness (Seidenari et al 1994;Eisenbeiss et al 1998), greater corneocyte surface area (Fluhr et al 2001), as well as lower surface roughness R a and higher furrow density of forearm skin (Lagarde et al 2005) have been reported for pre-menopausal women compared with men in the same age group. Until now, no significant gender differences have been reported for skin friction (Cua et al 1990(Cua et al , 1995Kenins 1994;Sivamani et al 2003c).…”
Section: Friction Experimentsmentioning
confidence: 99%
“…We attribute these variations to the menstrual cycle that is normally associated with changes in sex hormone levels (e.g. oestrogen), as well as in the water balance (Berardesca et al 1989;Eisenbeiss et al 1998). In the pre-menstrual phase, for example, the human body retains large amounts of salts and water.…”
Section: Friction Experimentsmentioning
confidence: 99%
“…Increases in skin thickness were seen in women on three-phase oral contraceptives during mid-cycle when taking a high dose of estradiol. The same was observed in women with a normal spontaneous menstrual cycle during days 12-22 when estradiol levels typically peak and remain high (Eisenbeiss, et al, 1998). A small number of studies have investigated the effect of water content on ligament behavior.…”
Section: Total Body Watermentioning
confidence: 77%